2006
DOI: 10.1177/07419325060270010401
|View full text |Cite
|
Sign up to set email alerts
|

Creative Problem Solving for General Education Intervention Teams

Abstract: Creative problem solving (CPS) is an approach for identifying solutions to problems within a structured, facilitated process. In the current studies, CPS was customized for general education intervention (GEI) teams in elementary schools. In the first study, 24 GEI teams were randomly assigned either to a CPS for GEI training condition or to a control group. Team outcome measures were tracked over the course of a school year, and the CPS for GEI teams consistently demonstrated superior performance relative to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Although the degree to which imagination can be enhanced is uncertain. Therefore help from the university will lead to innovation through several resources [66]. This study also analyzes the link between PCD, ATE, and EI.…”
Section: Discussion: Entrepreneurial Intention and Open Innovationmentioning
confidence: 99%
“…Although the degree to which imagination can be enhanced is uncertain. Therefore help from the university will lead to innovation through several resources [66]. This study also analyzes the link between PCD, ATE, and EI.…”
Section: Discussion: Entrepreneurial Intention and Open Innovationmentioning
confidence: 99%
“…Having a set agenda and process for the team meeting helps to ensure that the needed tasks will be completed within the time allotted. The role of a team facilitator is also essential (Doll et al, 2005; Hampton, 2004), as this person conducts the meeting and carefully monitors the time and the flow of the process (Bahr et al, 2006). Team members report that having an effective team facilitator is a key factor in both efficient and effective meetings (Hampton, 2004).…”
Section: Strategies For Maximizing Team Effectiveness and Efficiencymentioning
confidence: 99%
“…Unfortunately, the literature suggests that high‐quality team problem‐solving practices are more likely when implemented as part of a university or research‐based project (Doll et al, 2005). However, Bahr et al (2006) reported comparable outcomes for teams trained by statewide project staff and district trainers who had been part of a train‐the‐trainer program with project staff. It is important to note that both types of training (project staff and district trainers) also included follow‐up coaching with school teams that was provided by project staff.…”
Section: Strategies For Maximizing Team Effectiveness and Efficiencymentioning
confidence: 99%
“…In another study that compared the sustained implementation of Parent-Child Interaction Therapy (PCIT) following three training models (TT, learning collaborative, and distance education), therapists in the TT condition reported higher EBP penetration (i.e., greater number of patients treated with PCIT) compared to those in the other conditions [13]. In a study in the school setting, school teams trained via a TT approach to assist students with academic and behavior di culties using a problem-solving approach, scored higher on several indexes of team effectiveness (e.g., communicating clearly with one another; developing manageable interventions for teachers and students) compared to teams in control schools [15].…”
Section: Train-the-trainer Implementation Outcomesmentioning
confidence: 99%